Tool Wear Monitoring Technology and Its Application in Heavy Cutting - CHENG Yao-nan; DING Ya; GAI Xiao-yu; GUAN Rui; MA Chun-jie (Journal of Harbin University of Science and Technology)
In the modern cutting system, the wear or damage of cutting tools will lead to the failure of the workpiece and even the damage of machine tools.Tool condition monitoring can effectively improve the adverse effects of wear and breakage on the cutting process, so it is of great significance to apply tool condition monitoring to the process of heavy cutting water chamber head to improve the cutting efficiency and machining quality of workpieces. In order to discuss the tool wear monitoring technology and its application in heavy cutting, taking the common cutting tool wear monitoring as the research object, the most widely used and emerging key technologies, methods and principles in tool wear monitoring are deeply analyzed from the aspects of signal acquisition, feature processing, pattern recognition and decision control.Their advantages and disadvantages are analyzed in detail.Then the application of tool wear monitoring in heavy cutting are explained and analyzed.The achievements and progress made by domestic and foreign scholars in the field of tool wear monitoring are described, and the future development trend is prospected. Through the above research process, it provides theoretical and technical support for tool wear monitoring technology in heavy cutting process.